Health Care Hotspotting — A Randomized, Controlled Trial. Issue 6 (June 2020) - Finkelstein, Amy; Zhou, Annetta; Taubman, Sarah; Doyle, Joseph
Abstract : (Abstracted from N Engl J Med 2020;382:152–162) The United States is extremely disproportionate when it comes to health care spending per capita. Only 5% of the country's population is responsible for 50% of annual spending on health care–related costs.